PENGARUH INOVASI PRODUK DAN KUALITAS PELAYANAN TERHADAP MINAT PEMBELIAN : Studi pada Konsumen Richeese Factory di Lingkungan Universitas Kebangsaan Republik Indonesia Kota Bandung - Aprilia, Fani; Fithriani, Merry (Mansion: Management and Business on Kebangsaan, 2025)
Richeese Factory was chosen as the research site by the researcher. Richeese Factory has flourished in the era of sustainable development, introducing new products or modernized versions of existing ones, launching innovative products with new features to attract consumer interest in the environment of the National University of the Republic of Indonesia. The objective of this study is to determine the extent of the influence of Product Innovation and Service Quality on Purchase Intention, both partially and simultaneously. The research method employed in this study is descriptive and associative. The unit of analysis in this study is individual consumers of Richeese Factory in the environment of the National University of the Republic of Indonesia, Bandung City. The research findings indicate that there is a partial influence of Product Innovation and Service Quality on Purchase Intention among consumers of Richeese Factory in the environment of the National University of the Republic of Indonesia, Bandung City, with a significance value of 0.00 < 0.05. Simultaneously, Product Innovation and Service Quality significantly influence Purchase Intention, as evidenced by the calculated value of F 20.824 > F table 3.09 and a significance value of 0.000 < 0.05. The correlation coefficient (multiple R) value of 0.556 indicates a correlation between independent and dependent variables of 0.556. The coefficient of determination (R2) value of 0.309 means that the influence of Product Innovation and Service Quality on Purchase Intention is 30.9%, while the remaining 60.1% is influenced by other variables notexamined in this study.